Pendampingan Pengelolaan Pondok Pesantren Berbasis Boarding school: Studi Kasus di Arrisalah Boarding School Lombok Timur - Rahmi Kurniati; Ishak Ishak (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2026)
Islamic boarding schools (pesantren) have long played a strategic role in Islamic education in Indonesia and have increasingly transformed into modern educational institutions that integrate formal schooling with religious and character education. This study aims to describe and analyze educational management practices at Arrisalah Boarding school, East Lombok, as a pesantren implementing an integrated boarding school system. Using a qualitative descriptive approach based on field-based mentoring activities, data were collected through participatory observation, informal interviews, and documentation involving school leaders, teachers, boarding supervisors, and students. The study was conducted from October to December 2025. The findings indicate that Arrisalah Boarding school has implemented educational management effectively through the integration of the National Curriculum, JSIT curriculum, and pesantren curriculum, supported by a structured boarding school system. The Tahfiz Al-Qur’an program emerges as a core institutional identity and a key competitive advantage, contributing significantly to character building and public trust. Human resource management and student life in the dormitory further support a holistic educational environment. However, challenges remain in the management of facilities and pesantren business units, which require stronger planning, professional governance, and accountability. This study contributes empirically to the literature on modern pesantren management and provides practical insights for improving sustainable and quality-oriented educational management in Islamic boarding schools.